Старий та новий інституціоналізм у дослідженні правових інститутів - Несинова, Світлана Василівна; Несинова, Светлана Васильевна; Nesinova, Svetlana (Одеса : Юрид. л-ра, 2014)
This article analyzes the old (traditional) institutionalism and new institutionalism to justification the possibility of using an institutional approach to the methodology of the study of legal institutes within the legal system.
Несинова С. В. Старий та новий інституціоналізм у дослідженні правових інститутів / С. В. Несинова // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.) Ю. П. Аленін [та ін.] ; МОН України; НУ ОЮА. – Одеса : Юрид. л-ра, 2014. – Вип. 74. – С. 35-41.
Keywords: інституціоналізм; неоінституціоналізм; інститути; правові інститути; правова система; методологія дослідження; институционализм; неоинституционализм; институты; правовые институты; правовая система; методология исследования; institutionalism; new institutionalism; institutes; legal institutes; legal system; research methodology